Workplace interactions between people living with HIV and colleagues in Pampanga - Celis, Michael Louie C. (Animo Repository, 2014)
This study describes the workplace social interactions of People Living with HIV and their co-workers. Twenty five currently employed PLHIVs in Pampanga were invited to participate through in-depth, one-on-one interviews. The participants personal and work profiles, perceptions on health risks, and adjustments were gathered. Having been diagnosed with HIV, the interviewees expressed several concerns about threatening situations at work. Most of the perceptions of health risks are bio-psychological, non-use of protective precautions, and unhealthy behaviour and lifestyle. PLHIV experiences social setbacks which affect relationships at the workplace where interactions consist mostly of the supportive type. Forms of personalized stigmatization and discrimination experienced by the PLHIVs within their workplaces were also identified, most of which are self-inflicted and indirect, respectively. Aside from this, other difficulties encountered while interacting with their colleagues at the workplace were mostly occupational-health related. Results show that PLHIVs who are younger, from people-oriented industries, performing people-oriented tasks and those with shorter length of service have encountered more difficulties. In order to carry on with their work and career, PLHIVs and their colleagues make adjustments. The adjustment measures included mostly of time-based modifications. On the other hand, forms of reactions from colleagues from these adjustments are mostly amiable. And lastly, to maintain workplace interactions, PLHIVs make use of organizational actions to preserve their relationship with colleagues at work.